(2x + 4)(3x + 8)

Question

Asked 9/26/2012 6:34:58 AM

Updated 6/23/2018 10:13:14 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

debnjerry|Points 37623|

Question

Asked 9/26/2012 6:34:58 AM

Updated 6/23/2018 10:13:14 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Rating

8

(2x + 4)(3x + 8)

= 6x^2 + 16x + 12x + 32

=6x^2 + 28x + 32

= 6x^2 + 16x + 12x + 32

=6x^2 + 28x + 32

Added 6/23/2018 10:10:05 AM

This answer has been confirmed as correct and helpful.

8

(2x + a)(3x^2 + b)

= 6x^3 + 2bx + 3ax^2 + ab

= ab + 3ax^2 + 2bx + 6x^3

= 6x^3 + 2bx + 3ax^2 + ab

= ab + 3ax^2 + 2bx + 6x^3

Added 6/23/2018 10:11:23 AM

This answer has been confirmed as correct and helpful.

8

(r + s)(r^2 - rs + s^2)

= r^3 - r^2s + rs^2 + r^2s - rs^2 + s^3

= r^3 + s^3

= r^3 - r^2s + rs^2 + r^2s - rs^2 + s^3

= r^3 + s^3

Added 6/23/2018 10:12:50 AM

This answer has been confirmed as correct and helpful.

37,265,343

questions answered

There are no comments.